Análise ambiental de instalações para suínos em propriedades na região de Marechal Cândido Rondon-PR - Daga, Jacir (2005)
This work had as objective to evaluate the systems of management of manure swine s in the microcatchment of the Ajuricaba Stream, in properties that possess intensive swine creation. To identify to all the properties that possess swine creation, to select the properties that possess confined swine production and to evaluate the production of manure and the preexisting forms of treatment, to evaluate the individual necessities of readequaçion of the installations of each property, according to ambient norms in validity, to evaluate the final destination of the manure swine s, considering the class of risk of receiving ground of this material and to consider possible solutions for re-adequacies of the handling and the installations. The present study the southwest of the urban center of Marechal Cândido Rondon was carried through in the microcatchment Hydrographic of the Ajuricaba stream, located, between coordinates UTM SAD69, Spindle 21 x:793479 y:7281105, x:787107 y:7275685 and x:792943 y:7277182, being that the same one possess an area of 1.900 hectares, distributed in 110 lots, characterized for small properties the measure that 78% of them are minors who 25 hectares, using basically familiar man power. The work of surveys of the ambient, referring liabilities was become fulfilled to the clear bush, legal reserve, swine creation, as well as project of readequaçions in the suinícolas properties in the areas of the microcatchment of the Ajuricaba Stream, aiming at to the ambient adequacy of the same ones. The ten properties with intensive swine creation had been selected, for detailed analysis more of the forms of treatment of residues, deposition, form of storage, use and final destination of the residues generated in the place. The work of surveys of the ambient, referring liabilities was become fulfilled to the clear bush, legal reserve, swine creation, as well as project of readequaçions in the suinícolas properties in the areas of the microcatchment of the Ajuricaba Stream, aiming at to the ambient adequacy of mesmas.Com the data raised in each property, through georreferenciamento, with assists it of GPS, elaborated maps detailed with assists of Software CAD (Drawing Assisted for Compotator).Os resulted gotten allows to conclude that of the 110 analyzed properties, 10 properties work with intensive swine creation, no property makes the treatment of the swine manure of the correct form, eighty percent of the creator pig works with creation system termination and twenty percent with complete cycle, the analyzed installations do not possess the blade system of water, the cleanness of the installations are predominantly for scraping and basically daily, wastefulness of ration in 90% of the evaluated installations was not observed, the ground of the microcatchment supports application of dejections of a bigger number of animals 5 times that the current number.